Tinjauan Yuridis Akibat Hukum dalam Perbuatan Wanprestasi Perjanjian Pinjam Meminjam Uang : Studi Putusan PN Denpasar NO. 1302/PDT.G/2024/PN DPS - Ni Luh Yossi Shuartini Millenia; Komang Febrinayanti Dantes; Ni Komang Irma Adi Sukmaningsih (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
The term "breach of contract" in contract law refers to a breach of promise. Discussions of breach of contract, both in doctrine and jurisprudence, are usually associated with a statement of negligence by the debtor, where the debtor has failed to properly fulfill their contractual obligations, and the debtor is at fault. It must be acknowledged that a breach of contract, or breach of promise, already involves bad faith on the part of the party failing to fulfill their promise. The meaning of "breach of contract" in banking law relates to the occurrence of problem loans at banks, which cause the loan to become non-performing. This is usually due to the debtor or customer not paying by the previously agreed payment date. The existence of a breach of contract is inseparable from the existence of a credit agreement. Whether a debtor is in default cannot be determined simply because there are efforts to rescue loans that have entered a problematic stage. The beginning of a violation of an agreement or default due to someone not being paid, in meeting the credit rescue standards at the bank, usually efforts are made such as Rescheduling, Reconditioning, Restructuring, through this rescue, the debtor is given the opportunity to lose his business, so the concept of default in BW and the Banking Law must be measured through the performance given, in both regulations, then from there the concept of problem credit can be classified. This banking regulation can be said to be a default, the comparison of this concept is the discussion in this thesis.